Benthic Macroinvertebrate Survey in the Pak Phanang River Basin Affected by Anthropogenic Activities during February–November 2006 - Sakset, Amphorn; Sombunmak, Umporn (Agriculture and Natural Resources, 2012)
The objectives of this study were to assess macroinvertebrate diversity, to determine the ecological condition and to suggest any monitoring programs in the adversely affected area of the Pak Phanang River basin, southern Thailand. Seven years after a sluice had been constructed on the River, the study was conducted at different sampling sites (upper part, middle part and lower part of the river) and seasons (dry, early rainy and heavy rainy seasons). Twenty-two genera belonging to 20 families and 4 phyla were identiﬁ ed. Chironomus, Cerithidea and Thiara were the three genera most abundant. The Shannon-Wiener diversity index identiﬁ ed that the benthic diversity was generally at the medium level. The Biological Monitoring Working Party for Thailand and average score per taxon scores indicated that the ecological condition in this area can be considered to have fairly clean water with some pollution. Regular monitoring should be conducted especially during the low diversity period, that is in the middle part of the river during dry and heavy rainy seasons and in the upper part of the river during the early rainy season.